A systematic review and cohort study of operative training in general surgery - Elsey, Elizabeth (2019)
Surgical training in the UK has seen many changes over recent years with a move towards competency-based curricula requiring trainees to undertake workplace-based assessments and meet operative experience targets. Data from assessments and operative experience are collected routinely but have not been used to understand the outcomes of the UK national General Surgery specialty training programme. The aim of this thesis was to understand the operative experience of General Surgery specialty trainees in the UK.